"Bridging Old Relations": The (De)Construction of Ethnic Identity in the Educational Context of Bosnia and Herzegovina From the Teachers' Point of View. Issue 1 (2nd January 2017) - Kovač, Velibor Bobo; Tveit, Anne Dorthe; Cameron, David Lansing; Jortveit, Maryann
ABSTRACT: The present study focuses on an educational arrangement in Bosnia and Herzegovina (BiH) known as "two schools under one roof." The term refers to two different ethnic groups (Bosniaks and Croats) physically sharing the same school building, but maintaining separate administrations, teaching staff, and curricula. The purpose of the study is to explore the manner in which teachers (seven Bosniak and four Croat) from the two ethnic groups perceive and construct their group identities within this context. Findings indicate that the teachers' sense of belonging to different ethnic groups is strong and that the use of language functions as a vital marker for expressing group identity. In addition, satisfaction with the current situation and perceptions of interactions and discrimination differ substantially between the groups. We argue that this type of educational organization may reignite dormant tensions between the groups and accentuate ethnic differences in terms of (de)constructing ethnic identity.